PENGARUH PDB, INFLASI, DAN NILAI KURS TERHADAP TINGKAT PROFITABILITAS BANK SYARIAH (STUDI KASUS BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH YANG TERDAFTAR DI OJK 2010-2021): Indonesia - Figo Rahmansyah, Muhammad; Ashar, Khusnul (Islamic Economics and finance in Focus, 2023)
Banking is an important institution in a country, because it is banking that regulates all needs in our economic field such as transactions dan investments. save, banking. The bank itself is also one of the institutions that can overcome crises in a country, judging from the resilience to face crises, sharia banking has proven to be more resilient than conventional banks, judging from the various types of crises it has experienced, such as the 1998 crisis dan the crisis due to the Covid 19 pdanemic. therefore the growth of Islamic banking needs to be supported by its existence, to support the growth of Islamic banking, we must also avoid the health of Islamic banking itself, to ascertain whether a bank is healthy or not, we can judge it from a ratio called profitability which is represented by Return On Assets (ROA), dan the profitability ratio itself is influenced by internal dan external factors, in this study what will be built are external factors, namely inflation, GDP, dan exchange rates. The purpose of this research itself is to determine the short-term dan long-term effects of inflation, GDP, dan exchange rates on Islamic banking ROA using case studies of Islamic commercial banks registered with the OJK from 2010-2021. The result is that in the short term dan short term simultaneously there is a significant relationship between the Y variable, namely ROA dan variables such as inflation (X1), GDP (X2), dan exchange rate (X3), with a significance value of 0.000 for the long term dan short term where this value is greater than 0.005. Partially, in the short dan long term, inflation has a negative dan significant effect on Islamic banking ROA, while for the long dan short term, the exchange rate also has a negative dan significant effect on Islamic banking ROA, while for the long term dan short term, GDP has a positive dan significant effect. . Keywords: Inflation, Exchange Rate, GDP, Bank Profitability